Toward an Analysis of Pairwise Comparison Matrices with Z-number-valued Elements - Aliyev, Rashad R.; Huseynov, Oleg H.; Guliyev, Javanshir (Springer Science and Business Media Deutschland GmbH, 2022)
Pairwise comparison matrices (PCMs) encode preferences in decision problems. Decision-relevant information may be characterized by partial reliability. In this paper, PCMs with Z-number-valued elements are considered. It is proposed to analyze such matrices in terms of consistency and informativeness. An example is used to illustrate that these two requirements may be conflicting. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
11th International Conference on Theory and Applications Soft Computing, Computing with Words and Perceptions and Artificial Intelligence, ICSCCW 2021 -- 2021-08-23 through 2021-08-24 -- Antgalya -- 270799
Keywords: Consistency; Coverage measure; Pairwise comparison matrix; Specificity measure; Z-number